Effect of Different Durations of Home Bleaching on Tooth Discoloration Caused by Mineral Trioxide Aggregate: An In Vitro Study - K Saati; R Chitsazha; N Firouzi; S Tour Savadkouhi; N Firouzi (Islamic Azad University, 2023)
Background and Aim: Discoloration is an unfavorable side effect of regenerative endodontic procedures using mineral trioxide aggregate (MTA). The efficacy of home bleaching of discolored teeth with carbamide peroxide has not been well investigated, and the minimum required duration of home bleaching is still unclear. This study aimed to compare the effects of different durations of home bleaching on tooth discoloration caused by MTA.   Materials and Methods: This in vitro, experimental study used 16 tooth blocks of bovine central incisors. To cause discoloration, white MTA was applied for 40 days in cavities drilled in blocks. The color parameters were measured at baseline and at 14, 28, and 42 days after the application of 20% carbamide peroxide using a spectrophotometer. Data were analyzed by repeated measures ANOVA and Tukey's post-hoc test. Results: The color change (∆E) value was 22.9±10, 26.3±10.9, and 27.03±11 at 14, 28, and 42 days after bleaching, respectively. Significant color change occurred at 2, 4, and 6 weeks after the application of carbamide peroxide (P<0.001). The color change increased at 42 days (∆E of 3.1, or 13% compared with baseline), which was the highest amount among all time points. However, pairwise comparisons showed that it was not statistically significant (P=0.4). Conclusion: It appears that 14 days is the required time for bleaching of teeth discolored by MTA. Longer bleaching times showed insignificantly higher efficacy for tooth whitening.